BUDAYA KERJA GALIE: (Studi Kasus Budaya Kerja Kalangan Pegawai Negeri Sipil Etnik Minangkabau di Kabupaten Pasaman Barat) - Frinaldi, Aldri (Humanus, 2012)
The work culture of civil servants in this decentralization era tends to come fromthe working culture of each ethnic. The difference of culture applied causes thedifference of civil servants’ way, behavior, and action when performing their work. Thisresearch article aims to discuss one of the working cultures of the civil servants fromMinangkabau ethnic group named galie. This research was conducted by usingdescriptive-qualitative approach, and the data was collected trough observation,interview, and documentation study. Data is validated by triangulation and sourcetriangulation methods.Tthe data analysis is based on Miles and Huberman (2000). Theresult of the research shows that the galie work culture has usually been inherited in thefamily and society for a period time; hence the galie work culture is also implementedwhile working in the local government organization of Pasaman Barat regency. Theresearch concluded that the galie work culture does not cause work culture that canharm others, but whenever the work culture exists, the civil servants would be annoyed.Civil servants who have this work culture tend to avoid risks and prefer simpler workthan their colleagues.Key words: work ethnict culture, galie, civil servant, Minangkabau ethict